Relationship Between Knowledge Level About Anemia and Anemia Prevention Behavior Among Female Adolescents - Dwi Agustiana Sari; Jennifa Jennifa; Puji Rahayu (Open Access Health Scientific Journal, 2026)
Background: Anemia remains one of the leading nutritional health problems among adolescent girls and may negatively affect physical health, cognitive function, academic performance, and future reproductive outcomes. Adequate knowledge regarding anemia is expected to encourage adolescents to adopt appropriate preventive behaviors.Methods: This quantitative study employed a correlational design with a cross-sectional approach. The study was conducted at SMA N 2 Wates, Yogyakarta, Indonesia. The study population consisted of 357 female adolescents, and 189 participants were selected using proportionate random sampling. Data were collected using structured questionnaires assessing respondents' knowledge about anemia and anemia prevention behavior. Descriptive statistics were used to summarize respondents' characteristics, while Spearman's rank correlation test was performed to determine the relationship between knowledge and preventive behavior with a significance level of p<0.05.Results: Most respondents were 16 years old and were enrolled in grade X or XI. The majority demonstrated a moderate level of knowledge regarding anemia (52.4%) and moderate anemia prevention behavior (65.1%). Spearman correlation analysis revealed a statistically significant positive relationship between knowledge level and anemia prevention behavior (p<0.001; r=0.263), indicating that adolescents with better knowledge tended to demonstrate better preventive behavior despite the weak strength of correlation.Conclusion: There was a significant positive relationship between knowledge about anemia and anemia prevention behavior among female adolescents. Strengthening educational interventions within school health programs may improve adolescents' knowledge and encourage healthier behaviors to prevent anemia